A study of the stabilities, microstructures and fuel characteristics of tri-fuel (diesel-biodiesel-ethanol) using various fuel preparation methods - Lee, K.H.; N. A. M, Mukhtar; Hagos, F. Y.; M. M., Noor (IOP Publishing Ltd, 2017)
In this study, the work was carried out to investigate the effects of ethanol proportions on the stabilities and physicochemical characteristics of tri-fuel (Diesel-Biodiesel-Ethanol). For the first time, tri-fuel emulsions and blended were compared side by side. The experiment was done with composition having 5%, 10%, 15%, 20% and 25 % of ethanol with fixed 10% of biodiesel from palm oil origin on a volume basis into diesel. The results indicated that the phase stabilities of the emulsified fuels were higher compared to the blended fuels. In addition, tri-fuel composition with higher proportion of ethanol were found unstable with high tendency to form layer separation. It was found that tri-fuel emulsion with 5% ethanol content (D85B10E5) was of the best in stability with little separation. Furthermore, tri-fuel with lowest ethanol proportion indicated convincing physicochemical characteristics compared to others. Physicochemical characteristics of tri-fuel blending yield almost similar results to tri-fuel emulsion but degrading as more proportion ethanol content added. Emulsion category had cloudy look but on temporarily basis. Under the microscope, tri-fuel emulsion and blending droplet were similar for its active moving about micro-bubble but distinct in term of detection of collision, average disperse micro-bubble size, the spread and organization of the microstructure.